B-spline Interpolation Compared with Finite Difference, Finite Element and Finite Volume Methods Which Applied to Two-Point Boundary Value Problems - Çağlar, Hikmet; Çağlar, Nazan; Elfaituri, Khaled (ELSEVIER SCIENCE INC, 360 PARK AVE SOUTH, NEW YORK, NY 10010-1710 USA, 2006)
This paper considers the B-spline interpolation and compares this method with finite difference, finite element and finite volume methods which applied to the two-point boundary value problem. -d/dx(p(x)du/dx) = f(x), a < x < b, u(a) = u(b) = 0.
Keywords: Piecewise Polynomial; B-spline Interpolation; Finite Difference; Finite Element; Finite Volume; Numerical-Solution; Parçalı Polinom; B-spline Enterpolasyon; Sonlu Farklar; Sonlu Elemanlar; Sonlu Hacim; Sayısal Çözüm